JENIS, STRUKTUR, SERTA VARIASI TERJEMAHAN HATSUWA DAN DENTATSU NO MODARITI DALAM NOVEL KOGOERU KIBA KARYA ASA NONAMI - Sarungallo, Sarah Mayung (Humanis; Volume 7. No. 1. April 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The aim of this research is to describe kinds, structures, and translation variations of hatsuwa and dentatsu no modariti translation in the novel Kogoeru Kiba by Asa Nonami. The theories stated by Nitta Yoshio, Nida and Taber are used in this research. This research combined qualitative and quantitative method to analize the data. The result were presented formally and informally. The analysis result shows that there were 15 grammatical forms included in hatsuwa and dentatsu no modariti in the novel Kogoeru Kiba. They are imperative form, –kudasai form, –na form, –nasai form, –tai form, –shitakunai form, –youda form, –darou form, –deshou form, –kamoshirenai form, –nichigainai form, –souda form, –hazuda form, –ka form, and –no form. Each form has different pattern, and not all of the forms correspond with specific words, but some kinds of modality are translated into sentences which have the same nuance with the aims in using that modality. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Hatsuwa and dentatsu no modariti,, Kinds, Structure, Variation of Translation